Bilateral mandibular distraction in micrognathism or hypoplasia of mandible, hazrat fatemeh hospital - Mohammad-Esmaiil Hassani (Journal of Acute Disease, 2014)
Objective: To determine the results of Bilateral Distraction Osteogenesis (DO) versus traditional methods in treatment of micrognathia. Methods: During 6 years we had 67 patients with micrognathia. In group A, randomly 35 were treated with traditional methods (Saggital osteotomy and/or bone grafts) and group B 32 cases were treated with Bilateral External Distraction Osteogenesis. Follow up was 36+/− 6 months. X-Ray, CT scan and cast modelling were done for all of the patients. SNA, SNB angles were measured in cephalograms. The patients were examined after one, two, three, six, 12 months for any complications and signs of bone resorption and relapse. Bony and soft tissue advancements were measured and compared with each other. Results: During 6 years we had 67 patients with class II malocclusion. Mean SNA angle in group A was 80.8 (80–81.5) and 80.9 (80–82) in group B. Mean SNB angle in group A was 77.6 (76.5–78) and 77.4 (76.5–78.5). After treatment mean SNB in group A was 79.1 and the difference was significant comparing to pre-op measurement (P<0.005). Mean SNB in group B after treatment was 79.2 which was significantly different comparing with SNB angle before surgery. The mean SNA in both group were not statistically and significantly different. The mean SNB after surgery in both group were not statistically and significantly different. Mean Mandibular advancement in group A was 11.9 mm (7.5–18 mm) and group B with DO treatment was12.1 mm (8–19 mm) which was not significantly different. The patient in group A evaluate the surgical results as excellent (60%) and good (28.5%). The patient in group B evaluate the results as excellent (78.1%) and good (15.6%). Conclusion: The Bilateral Distraction Oseogenesis method can bring forwards the retruded mandible effectively and its results has no difference with older methods. It is an effective and reliable procedure for hypoplasia of Mandible and the results are comparable with older methods.